2021
DOI: 10.1002/capr.12389
|View full text |Cite
|
Sign up to set email alerts
|

Exploring virtue ethics in psychodynamic psychotherapy: latent changes in humility, affect regulation, symptoms and well‐being

Abstract: A virtue ethics premise is that flourishing cannot be achieved solely through symptom reduction, but, rather, is inextricably connected with the development of 'qualities of human character and excellence which enhance the capacity to live well' (Sandage & Hill, 2001, p. 243). Sometimes also described as character strengths, virtues are grounded in motivational, affective, cognitive, relational, behavioural and contextual dimensions of human functioning, and thus hold important implications for therapists' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 67 publications
3
18
0
Order By: Relevance
“…Our findings addressed the need for further empirical research on humility and well-being in outpatient mental health contexts (Jankowski, Captari, et al, 2021;Paine et al, 2018), and we offer two primary implications for the assessment and potential treatment of religious leaders. First, emotion regulation appears to be a key construct in recent empirical research on virtue and well-being (Jankowski, Captari, et al, 2021), and emotion has played a prominent role in many moral philosophies related to virtue (Kristjansson, 2018). In addition, Sandage et al (2015) surmised that grandiosity can function as a defense mechanism or coping strategy against emotional dysregulation, indicative of an instrumental or utilitarian approach to relationships.…”
Section: Practical Implicationsmentioning
confidence: 75%
See 2 more Smart Citations
“…Our findings addressed the need for further empirical research on humility and well-being in outpatient mental health contexts (Jankowski, Captari, et al, 2021;Paine et al, 2018), and we offer two primary implications for the assessment and potential treatment of religious leaders. First, emotion regulation appears to be a key construct in recent empirical research on virtue and well-being (Jankowski, Captari, et al, 2021), and emotion has played a prominent role in many moral philosophies related to virtue (Kristjansson, 2018). In addition, Sandage et al (2015) surmised that grandiosity can function as a defense mechanism or coping strategy against emotional dysregulation, indicative of an instrumental or utilitarian approach to relationships.…”
Section: Practical Implicationsmentioning
confidence: 75%
“…We tested our proposed moderated mediation model with a sample of clergy candidates receiving a psychological evaluation at a community mental health center as part of their vocational discernment process. We therefore draw attention to client humility, and address the neglect of research on client humility, relative to the growing literature on clinician humility and the effectiveness of mental health treatment (Jankowski, Captari, et al, 2021).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Humility lies at the heart of religion, as Christian scholars St. Augustine and St. Thomas Aquinas have advocated, and has also been linked to several favorable outcomes, including health (Krause 2010 ; Jankowski and Sandage 2014 ), better social relationships (Davis et al 2013 ; Van Tongeren et al 2014 ) and more effective job performance and organizational leadership (Johnson et al 2011 ; Lee et al 2019 ; Howard and Van Zandt 2020 ). Given both theological and social scientific interest in humility, we sought to expand on a growing base of empirical evidence linking religion/spirituality and humility (see Davis et al 2014 , 2017 ; Jankowski et al 2021 , 2022 ; Rowatt et al 2014 ; Van Tongeren et al 2016 , 2018). In the current study, we considered how one aspect of religion/spirituality, perceptions of God-mediated control, may be an additional precursor to humility.…”
Section: Discussionmentioning
confidence: 99%
“…Interweaving a virtue and well-being focus-contextualized to a client's SERT context-within clinical formulation and treatment has significant potential, but it is much more difficult to study and thus is less empirically developed. As one example, a recent practice-based study found that clients in psychodynamic therapy evidenced growth in humility, which predicted changes both in symptoms and well-being (Jankowski et al, 2021). For some clients, virtues may be a relevant explicit focus (e.g., integrating the REACH Forgiveness model into therapy); for others, virtues may emerge within the treatment process (e.g., the therapist embodies humility amidst an alliance rupture).…”
Section: Attend To the Complexities Of Real-world Clinical Practicementioning
confidence: 99%